The impact of conflict on the socio-economic development of Libya - Manuel, Tanaka (Midlands State University, 2019)
The research analyzed the problems and effects of conflict on the socio-economic development using Libya as a case of reference. The purpose of the study was to highlight how conflict derails socio-economic development and encourage nations to resort to peace constantly. The Libyan conflict was a composition of diverse varied issues and differences between the Government and its citizens, between 2010 and 2014. The conflict derailed and disrupted the daily operations of the economy which then affected the well being of the state as well. The Libyan conflict surrounded the nation with an atmosphere that was not conducive and productive for the socio-economic development to stand on its feet. The study shed light on the negative effects posed on the socio-economic development of a nation by conflict in a bid to discourage the occurrence of conflict. It also highlighted how conflict ridden countries can better handle themselves when they are already in conflict. Diverse and varied issues, grievances as well as differences were said to be the major challenges to conflict free nations. Focus group discussions were employed to capture perspectives and opinions of political activists, economic experts and an interview was thrust into the mix to also include the insight of a social commentator. Content analysis and thematic analysis were combined to examine and analyze the respondents’ reviews and their input in the study. All this helped in explaining the research findings with the respondents in consent that conflict had a detrimental effect of the operation of an economy, governments had to prioritize its citizens in order to avoid conflicts and making it easy for their social stances and economies to perform better in a conflict environment. Some of the recommendations that were suggested by the study to conflict ridden countries are to play by the parameters set out for fighting by the UN and pay attention to conflict indicators and signals.